Stress as a major determinant of migraine in women aged 25-65 years - Woro Riyadina; Lelly Andayasari (Faculty of Medicine, Universitas Trisakti, 2014)
BACKGROUNDMigraine is a primary headache causing substantial disability in patients. The prevalence of migraine in women is still high. Menarche, menstruation, pregnancy, menopause, and the use of hormonal contraceptives and hormone replacement treatment may influence migraine occurrence. The aim of this study was to determine the major determinants of migraine in adult women aged 25-65 years.METHODSA cross-sectional study of 2,747 women from the baseline study “Cohort Study of Risk Factors for Non-Communicable Diseases”. The dependent variable was migraine based on the diagnosis of health providers or symptoms. Independent variables were demographic (age, marital status, education) and behavioral (smoking, diet, and stress) characteristics, metabolic disorders (obesity, hypertension, dyslipidemia), and hormonal factors (contraception and hormone therapy). Data were collected through interviews (characteristics, health and hormonal status, diet), measurement (anthropometrics, blood pressure), and health examination (blood specimens, neurology). Data were analyzed by chisquare test and multiple logistic regression.RESULTSMigraine in adult women was found in 710 cases (25.8%) with symptoms ofworsening with activity (15%), nausea and vomiting (13%), and photophobia/ phonophobia (4.1%). The main determinant of migraine in adult women was stress with a 2.47-fold risk [95% CI = 2.07 to 2.95] as compared with no stress, after controlling for smoking, menstruation and hormonal drug consumption.CONCLUSIONStress is a major determinant of migraine in adult women, therefore healthprograms should be instituted through health promotion, prevention and education to control stress.